Keberkesanan Dalam Penyampaian Khutbah Jumaat Dengan Penghayatan Bahasa Melayu, Satu Kajian di Wilayah Yala - Khoya, Moohamad; Ardam, Syafie (Al-HIKMAH Journal, 2018)
The propose of this article is to study the effectiveness of Friday Khutbah with local Malay language conservation by Khatib. This work applies descriptive research method to analyse and interviews the person in charge of the Khutbah presentation. The result shows that 1) 95% of Khatibs keep presenting Khutbah with standard and local Malay language and spend 15 to 20 minutes. 2) 5% of Khatibs use the combination of Thai and Malay language or only Thai language in preaching up to the characteristic of people at those areas. 3) Khutbah presentation affects people in many ways both internal and external which Khatib should has a role to make sure that the audiences gain knowledge, understanding and can improve their life. However, the better effectiveness would come from the effective preparation, knowledge and the presentation skill of Khatib in Khutbah.